Acupuncture with Or without Combined Auricular Acupuncture for Insomnia: A Randomised, Waitlist-Controlled Trial. Issue 1 (February 2018) - Chung, Ka-Fai; Yeung, Wing-Fai; Yu, Branda Yee-Man; Leung, Feona Chung-Yin; Zhang, Shi-Ping; Zhang, Zhang-Jin; Ng, Roger Man-Kin; Yiu, Gar-Chung
Background: Few high-quality, large-scale, controlled trials comparing the effectiveness and safety of acupuncture, auricular acupuncture and combined acupuncture treatment for insomnia are available. Objective: To carry out a randomised, assessor-blinded, waitlist-controlled trial to test the superiority of combination treatment. Methods: After in-person and polysomnography screening, 224 subjects (mean age 53.4 years; 75.4% female) with DSM-5 insomnia disorder, who were free from major psychiatric disorders and with sleep-diary-derived sleep efficiency averaged over 1 week of <85%, were randomised to acupuncture alone, acupuncture plus auricular acupuncture (combination treatment), or a waitlist in a 3:3:1 ratio. Standardised acupuncture and combination treatment were provided three times weekly for 3 weeks. The primary outcome was sleep-diary-derived sleep efficiency. Secondary outcomes included wrist actigraphy and self-reported scales on insomnia, anxiety and depression, fatigue, sleepiness and functioning. Assessments were conducted at baseline, 1 week, 4 weeks and 13 weeks after treatment. Participants on the waitlist were re-randomised to receive acupuncture or combination treatment after the second post-baseline assessment. Results: There was no significant difference between acupuncture and combination treatment in the primary outcome and most secondary outcomes at all time points. However, both treatments were better than waitlist in reducing insomnia, anxiety/depressive symptoms and fatigue, and improving function. Within-group improvements were maintained at 13 weeks after treatment. Of 260 adverse events, 243 were mild (93.5%). Discontinuation due to adverse events was 2.1% and 3.1% for acupuncture and combination treatment, respectively. Conclusions: Limited by short-term treatment and follow-up, the attempt to augment acupuncture by auricular acupuncture was not supported. Acupuncture and combination treatment were safe and had mild hypnotic effects, which lasted for at least 13 weeks. Trial Registration Number: NCT01891097; Results.